Pengaruh Kualitas Produk, Store Atmosphere dan Brand Reputation Terhadap Loyalitas Konsumen Pada Cafe Kali and Resto Bandar Lampung - Fahreza Rizky Pratama; Tri Lestira Putri Warganegara (Center of Economic Students Journal, 2026)
Competition in the culinary sector requires maintaining customer loyalty to ensure business sustainability. Cafe Kali and Resto Bandar Lampung experienced monthly customer fluctuations throughout 2024 and low sales growth, averaging only 0.80 percent per month, well below the company's target of 5 percent. This condition indicates that customer loyalty has not been optimally formed. This study aims to analyze the influence of product quality, store atmosphere, and brand reputation on customer loyalty at Cafe Kali and Resto Bandar Lampung. The research uses a quantitative survey approach, collecting data by distributing questionnaires to consumers. The data analysis technique uses multiple linear regression analysis to determine the influence of each variable, both partially and simultaneously. The results of the study are expected to provide an overview of the factors that most influence customer loyalty and to inform management in formulating marketing strategies to increase visit stability and sales growth.